Curvature change of moving bodies and its application for development of protective elements for protective clothing - Dominik Münks; Yordan Kyosev; Xia Shuang (Communications in Development and Assembling of Textile Products)
When the human body moves, the body curvatures always change on the corresponding parts of the body. For ideal protective clothing, body curvatures during different movements have to be taken into account, as they influence the protection and the wearing comfort. For this reason, this study will focus on demonstrating methods to visually display such curvature changes. The changes are visually shown in different poses. The aim is to use this method to optimize protective elements on body parts with increased curvature changes. This would make protective clothing safer and more comfortable to wear.